Training of Basic Skills of Writing Scientific Using Mendeley Software and Pharaprase Techniques - Pratama, Aditya; Wolor, Christian Wiradendi (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2022)
Community Service is a form of response from a lecturer to Contribute to Improving the quality of the community. Community services be wrong one obligation a lecturer that Stated of deep Tri Dharma College Tall. Lecturer Required can Increase quality self and customize with development science knowledge. Activities community services be container Distribution science knowledge. Lecturer transfers knowledge that is Owned through Activities that are Compiled automatically methodical. Harapanya with the existence of Activities that are already Structured with good Expected transfer of science knowledge get executed automatically optimally. Community services that already Implemented be enter Into Devotion regkognisi. Community services this Implemented at the University Halu Oleo, STIE Pertiwi, and STIAB Lampung which already have Collaborate with Faculty Economics State University of Jakarta. Community services that Themed regkognisi be wrong one proof that there is Follow further from collaborated that already Done. As for the Activities that are Done be given Training Form Skills Use software mandelay and Engineering phrase with method Talk, practice and ask and answer. The aforementioned training Expected will be able to Increase the quality or ability of lecturer deep write scientific work.